Diagnostic value of nucleic acid amplification tests on bronchoalveolar lavage fluid for smear-negative pulmonary tuberculosis: a meta-analysis. Issue 4 (29th July 2015) - Tian, Panwen; Shen, Yongchun; Wang, Ye; Wan, Chun; Feng, Mei; Zhu, Jing; Yang, Ting; Chen, Lei; Wen, Fuqiang
Abstract : Based on current available evidence, NAAT on BALF plays a role in the diagnosis of smear-negative pulmonary tuberculosis, and further studies should be performed to confirm our findings.. Abstract : The diagnosis of smear-negative pulmonary tuberculosis (SNPT) remains a clinical challenge. Many studies suggest that nucleic acid amplification tests (NAATs) on bronchoalveolar lavage fluid (BALF) plays a role in diagnosing SNPT, but with considerable varying results. The current study aimed to summarize the overall diagnostic accuracy of NAATs assay on BALF for SNPT. A systematic literature search was performed and data were retrieved. Pooled sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR) and diagnostic odds ratio (DOR) were calculated. A summary receiver operating characteristic curve and area under the curve (AUC) were used to evaluate the overall diagnostic performance. All the statistical analysis was performed by using STATA 12.0 and Meta-DiSc 1.4 software. A total of nine studies with 1214 subjects were included this meta-analysis. The pooled sensitivity, specificity, PLR, NLR and DOR were 0.54 [95% CI (confidence interval): 0.48–0.59], 0.97 (95% CI: 0.95–0.98), 12.13 (95% CI: 8.23–17.88), 0.36 (95% CI: 0.23–0.56) and 44.71 (95% CI: 22.30–89.63) respectively. The AUC was 0.96. Estimated positive and negative post-probability values for a SNPT prevalence of 20% were 82% and 7% respectively. No publication bias was identified. Current available evidence indicated that NAATs on BALF may play a role in diagnosing SNPT, whereas the results should be interpreted in parallel with clinical information of patients and the results of traditional tests. Further studies should be performed to confirm our findings.